Cardiac Autonomic Neuropathy as a Result of Mild Hypercaloric Challenge in Absence of Signs of Diabetes: Modulation by Antidiabetic Drugs. (31st January 2018) - Al-Assi, Ola; Ghali, Rana; Mroueh, Ali; Kaplan, Abdullah; Mougharbil, Nahed; Eid, Ali H.; Zouein, Fouad A.; El-Yazbi, Ahmed F.
Abstract : Cardiac autonomic neuropathy (CAN) is an early cardiovascular complication of diabetes occurring before metabolic derangement is evident. The cause of CAN remains elusive and cannot be directly linked to hyperglycemia. Recent clinical data report cardioprotective effects of some antidiabetic drugs independent of their hypoglycemic action. Here, we used a rat model receiving limited daily increase in calories from fat (HC diet) to assess whether mild metabolic challenge led to CAN in absence of interfering effects of hyperglycemia, glucose intolerance, or obesity. Rats receiving HC diet for 12 weeks showed reduction in baroreceptor sensitivity and heart rate variability despite lack of change in baseline hemodynamic and cardiovascular structural parameters. Impairment of cardiac autonomic control was accompanied with perivascular adipose inflammation observed as an increased inflammatory cytokine expression, together with increased cardiac oxidative stress, and signaling derangement characteristic of diabetic cardiomyopathy. Two-week treatment with metformin or pioglitazone rectified the autonomic derangement and corrected the molecular changes. Switching rats to normal chow but not to isocaloric amounts of HC for two weeks reversed CAN. As such, we conclude that adipose inflammation due to increased fat intake might underlie development of CAN and, hence, the beneficial effects of metformin and pioglitazone.